«Բեկոր» իմաստով հայերեն մի քանի բառերի ստուգաբանություն - Զաքարյան, Հովհաննես (ՀՀ ԳԱԱ ԼԻ հրատարակչություն)
The article, dwelling upon phonetic, morphemic and semantic analyses, puts forward the following new etymologies of words that all come from the PIE root *(s)keu- “to cut, to split” <*sek- “to cut, cut off, sever”: ջարդ-ել “to break, to smash, to hack” <*sk՛whǝ-r-դ-, ջախ-ել “to destroy, to smash, to wreck, to break up” <*sk՛whǝkh-, ճոթ “1, piece, part, 2, edge” <*sk՛ho-t-, ճիմ “sod, divot” <*sk՛hē-m-, ճութ “bunch” *sk՛hō-t-, ճիռ “small bunch” <*sk՛hē-r-s-, ծոպ “fringe” <*(s)k՛ho-b-, ծիւ (ծուէն) “scrap, shred” <*(s)k՛hēu-, քց-իմ “hangnail” <*(s)kē-k՛s-, քեղ-ել “to peel” <*(s)ke-l-, կաս-ուլ “chop the wheat” <*(s) kə-k՛-, կաս-ել “cease, stop” <*(s)kə-k՛-, խոտ-ել “reject” <*(s)kho-d- etc. В настоящей статье на основе фонетического, словообразовательного и семантического анали- зов предлагаются следующие новые этимологии слов, которые все происходят от ПИЕ корня *(s)keu- “резать, раскалывать” <*sek- “отрезать, разорвать”: ջարդ-ել “сломать, разбить” <*sk՛whǝ-r-դ-, ջախ-ել “крушить, громить, разбить” <*sk՛whǝ-kh-, ճոթ “1, кусок, часть, 2, край” <*sk՛ho-t-, ճիմ “дёрн” <*sk՛hē-m-, ճութ “гроздь, кисть” <*sk՛hō-t-, ճիռ “маленькая гроздь, кисть” <*sk՛hē-r-s-, ծոպ “бахрома” <*(s)k՛ho-b-, ծիւ (ծուէն) “клочок, лоскуток” <*(s)k՛hēu-, քց-իմ “заусеница” <*(s)kēk՛s-, քեղ-ել “шелушить” <*(s)ke-l-, կաս-ուլ “нарезать пшеницу” <*(s)kək՛-, կաս-ել “перестать, прекратиться” <*(s)kə-k՛-, խոտ-ել “отклонять” <*(s)kho-d- и т. д.
Keywords: Լեզվաբանություն; Ստուգաբանություն